Bioliquids and their use in power generation – A technology review. (September 2020) - Seljak, T.; Buffi, M.; Valera-Medina, A.; Chong, C.T.; Chiaramonti, D.; Katrašnik, T.
Abstract: The first EU Renewable Energy Directive (RED) served as an effective push for world-wide research efforts on biofuels and bioliquids, i.e. liquid fuels for energy purposes other than for transport, including electricity, heating, and cooling, which are produced from biomass. In December 2018 the new RED II was published in the Official Journal of the European Union. Therefore, it is now the right time to provide a comprehensive overview of achievements and practices that were developed within the current perspective. To comply with this objective, the present study focuses on a comprehensive and systematic technical evaluation of all key aspects of the different distributed energy generation pathways using bioliquids in reciprocating engines and micro gas turbines that were overseen by these EU actions. Methodologically, the study originates from the analyses of feedstock and fuel processing technologies, which decisively influence fuel properties. The study systematically and holistically highlights the utilisation of these bioliquids in terms of fuel property specific challenges, required engine adaptations, and equipment durability, culminating in analyses of engine performance and emissions. In addition, innovative proposals and future opportunities for further technical improvements in the whole production-consumption cycle are presented, thus serving as a guideline for upcoming research and development activities in the fast-growing area of bioliquids. Additionally, the paper systematically addresses opportunities for the utilisation of waste streams, emerging from the ever increasing circular use of materials and resources. With this, the present review provides the sorely needed link between past efforts, oriented towards the exploitation of bio-based resources for power generation, and the very recent zero-waste oriented society that will require a realistic exploitation plan for residuals originating from intensive material looping. Highlights: A systematic and holistic assessment of relevant properties of bioliquids. New technical advances of piston engines and micro gas turbines using bioliquids. A detailed analysis of required power system adaptations imposed by bioliquids. Future perspectives for power generation with bioliquids in a circular economy.